Impaired Placentation and Early Pregnancy Loss in Patients with MTHFR Polymorphisms and Type-1 Diabetes Mellitus. (3rd September 2019) - Gurbuz, Rumeysa Hekimoglu; Atilla, Pergin; Orgul, Gokcen; Tanacan, Atakan; Dolgun, Anil; Cakar, Ayse Nur; Beksac, Mehmet Sinan
Abstract: Objective: To evaluate the impact of type-1 diabetes mellitus (DM) and methylenetetrahydrofolate reductase (MTHFR) polymorphisms on impaired placentation leading to early pregnancy loss.Methods: Miscarriage materials were obtained from eight pregnant women with type-1 DM without MTHFR polymorphism, eight with MTHFR polymorphisms without type-1 DM, and eight controls with neither DM nor MTHFR polymorphisms. Insulin-like growth factor-1 (IGF-1), leukemia inhibitory factor (LIF), and Beclin-1 expression were assessed to evaluate placentation.Results: Cytoplasmic LIF, IGF-1, and Beclin-1 expression were decreased in the superficial and glandular epithelial cells of the decidua in both study groups. LIF expression was increased in interstitial trophoblasts in the MTHFR group. IGF-1 expression was decreased in the decidual cells and interstitial trophoblasts in both study groups, while the decrease in stromal cells was noted only in type-1 DM group. Beclin-1 expression was increased in interstitial and villous trophoblasts in both study groups.Conclusion: The expression of IGF-1, LIF, and Beclin-1 are altered in both the decidua and the trophoblasts in pregnancies of women with type-1 DM and MTHFR polymorphisms, compared to normal pregnancies undergoing (elective) terminations.